Ancestors and Relatives : Genealogy, Identity, and Community - Zerubavel, Eviatar (Oxford University Press, 2012)
Genealogy has long been one of humanity's greatest obsessions. But with the rise of genetics, and increasing media attention to it through programs like Who Do You Think You Are? and Faces of America, we are now told that genetic markers can definitively tell us who we are and where we came from. The problem, writes Eviatar Zerubavel, is that biology does not provide us with the full picture. After all, he asks, why do we consider Barack Obama black even though his mother was white? Why did the Nazis believe that unions of Germans and Jews would produce Jews rather than Germans? In this provoc.